1975
DOI: 10.1016/0035-9203(75)90110-8
|View full text |Cite
|
Sign up to set email alerts
|

Micro-organisms in filarial larvae (Nematoda)

Abstract: Unusual bodies have been described in the hypodermal tissues of larval Dirofilaria immitis and Brugia pahangi. Ultrastructural evidence indicates that these bodies are probably Gram-negative micro-organisms. It appears that the presence of large numbers of these bodies in an early embryo may affect development adversely. Their importance at later stages of development of filariae is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
82
0
3

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 11 publications
7
82
0
3
Order By: Relevance
“…In animals, heartworm disease of dogs and cats is caused by another ¢larial nematode, Diro¢laria immitis. Intracellular bacteria have been observed in various species of ¢larial nematodes, including D. immitis, D. repens, O. volvulus, B. malayi, and B. pahangi (McLaren et al 1975;Vincent et al 1975;Kozek & Marroquin 1977). There is evidence that these bacteria are transmitted transovarially, in that they have been observed in oocytes, developing eggs, and micro¢lariae in D. immitis and O. volvulus (McLaren et al 1975;Kozek & Marroquin 1977;Sironi et al 1995).…”
Section: Introductionmentioning
confidence: 94%
“…In animals, heartworm disease of dogs and cats is caused by another ¢larial nematode, Diro¢laria immitis. Intracellular bacteria have been observed in various species of ¢larial nematodes, including D. immitis, D. repens, O. volvulus, B. malayi, and B. pahangi (McLaren et al 1975;Vincent et al 1975;Kozek & Marroquin 1977). There is evidence that these bacteria are transmitted transovarially, in that they have been observed in oocytes, developing eggs, and micro¢lariae in D. immitis and O. volvulus (McLaren et al 1975;Kozek & Marroquin 1977;Sironi et al 1995).…”
Section: Introductionmentioning
confidence: 94%
“…Early workers hypothesized a pathogenic effect, because some embryos appeared distorted by the number of bacteria they carried (5). This was not proved, however, Intracellular bacteria have been described in several species of filarial nematodes, but their relationships with, and effects on, their nematode hosts have not previously been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria appeared to be vertically transmitted by inclusion with the oocyte during development, and infection was highly prevalent in species carrying the bacteria. Few species of filariae (e.g., Acanthocheilonema viteae) did not appear to harbor bacteria (5). Molecular phylogenetic analysis has recently shown that the intracellular bacteria of Dirofilaria immitis, the dog heartworm, are closely related to the cytoplasmic incompatibility endobacteria of arthropods, of the genus Wolbachia (order Rickettsiales) (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wolbachia is a group of endosymbiotic bacteria belonging to the order Rickettsiales, had been detected in majority of filarial species studied so far [5]. The discovery of Wolbachia in filarial species has provided a new promising target for the chemotherapy of human filariasis [6].…”
Section: Introductionmentioning
confidence: 99%